O exercício físico autorregulado, em ambiente quente, nãoaumenta o estresse oxidativo nem reduz o desempenho - Michele Macedo Moraes (2010)
Fatigue has been thought, according to integrated models, as a protector mechanism that causes the end of the exercise or the decline in physical work capacity, before any kind of homeostasis failure. Usually, the ambient temperature and the accumulation of metabolic products are integrated factors involved in fatigue. A possible metabolic product, which influences performance, is the reactive oxygen species (ROS). The aim ofthis study was to investigate the individual performance in a warm and a temperate ambient, during a self-paced exercise and to estimate the ROS influence in fatigue. Some days before the exercise bout, nine subjects (26,89 ± 1,32 years old) voluntarily performed a progressive test to evaluate the maximal power output and to become familiar with the test protocol used during the trial. During the test days, the subjects stayed 20 minutes in rest and performed 20 minutes of self-paced exercise in bicycle, in a temperate (23ºC / 62% URA) or in a warm (34ºC / 65% URA) ambient. The ambient did not influence the performance or the perception of effort (PSE). In the end of self-paced protocol, the rectal temperature the internal temperature indicator that is concordant with tympanic temperature was higher in the warm trial, but the heat storage wassimilar in both conditions. The following thermoregulation adjustments to heat dissipation, on warm ambient, were observed: increasing in skin temperature and in heart rate. The lactate concentration increased during exercise in both situations; glucose decreased and ROS production by diacylglycerol protein kinase C (DAG-PKC) increased only during warm exercise trial. Despite the fact that ROS capacity production increased, the antioxidant or malondialdehyde (MDA) concentration did not change. Theresults of the present study showed that the modifications in some physiological responses because of the warm ambient were not sufficiently strong to decrease the exercise performance.